HOST PREFERENCE OF DERMESTES MACULATUS DEGEER (COLEOPTERA : DERMESTIDAE) AN IMPORTANT PEST OF STORED DRIED FISH IN TRIPURA - NATH, S.; PANDE, Y.D.; GHOSH, D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
Host preference of Dermestes maculatus DeGeer (Coleoptera : Dermestidae) was studied on nine different commonly available and popular dried fish species of Tripura, during favourable insect infestation period, March - June 1997 and 1998. It was found that no larva developed on Raconda russeliana. Variation of total developmental period on different tested dried fish species was due to the variation of larval period. The different indices suggested that the most preferred dried fish species were Pseudeutropius sp. followed by Mystus vittatus, Mystus sp., Lepturacanthus savala, Carangoides sp., Harpodon nehereus, Puntius sp. and Coilia neglecta.